Analisis Ilustrasi Manajemen Pelatihan dan Keterampilan Pekerja Tambang Di PT. Semen Baturaja (Persero) Tbk. (Sebuah Pendekatan Deskriptif Terhadap Implementasi dan Peran Manajemen Pelatihan dan Keterampilan Pada SDM Tambang) - Rizal Fahmi; Eddy Ibrahim; Maulana Yusuf (Dinasti Research, 2025)
Mining workers are crucial human resources in operating mining production processes, in addition to machinery and digital equipment. These workers possess specialized, specific, and complex skills, facing significant risks both to human lives (mortality) and corporate assets. Therefore, nurturing, developing, and enhancing their well-being, particularly in knowledge and skills (both soft skills and hard skills), are the main focus of this study. This research aims to illustrate the management of training and skills for mining workers at PT. Semen Baturaja (Persero) Tbk. and analyze it descriptively in terms of realization, achievements, and objectives. The subjects of this research are the Operation and Waste Management divisions at SMBR. This study employs a qualitative method with data collection techniques involving triangulation, yielding findings that show: 1) Training and skills are worker competency standards, 2) Training and skills are necessary to fulfill competency and certification requirements, 3) Training is tailored to job positions, and 4) Competency evaluation and job rotation practices are implemented. The conclusion is that SMBR has adequately implemented training and skill management, covering both soft and hard skills. Hard skills are reflected in training aligned with Ministerial Regulation of Energy and Mineral Resources (Permen ESDM) No. 1827, while soft skills are included in in-house training implementation.